The Efficacy and Safety of Rituximab for Childhood Steroid-Dependent Nephrotic Syndrome: A Systematic Review and Meta-Analysis - Liu, Sidi; Gui, Chuying; Lu, Zhenzhen; Li, Huijie; Fu, Zhike; Deng, Yueyi (Frontiers in Pediatrics, 2021)
Objectives: Rituximab (RTX), a possible alternative treatment option, is recognized as a new therapeutic hope for the treatment of steroid-dependent nephrotic syndrome (SDNS) in children. However, the efficacy and safety of RTX in the treatment of childhood SDNS are still controversial. The objective of this study was to evaluate the efficacy and safety of RTX treatment in children with SDNS. Study design: Six randomized controlled trials (RCTs) and one retrospective comparative control study data from studies, performed before January 2021 were collected, from PubMed, Cochrane Library, Embase, and Web of Science. The studies evaluating the efficacy and safety of RTX in childhood SDNS were included. Results: Six RCTs and one retrospective comparative control study were included in our analysis. Compared with the control group, the RTX treatment group achieved a higher complete remission rate (OR=5.21; 95% CI 3.18 to 8.54; P<0.00001), and we found significant differences between the two groups on serum albumin level (MD=0.88; 95% CI 0.43 to 1.33; P=0.0001) and estimated glomerular filtration rate (MD=6.43; 95% CI 2.68 to 10.19; P=0.0008). However, RTX treatment did not significantly lower serum creatinine levels, nor did it significantly reduce the occurrence of proteinuria. And we found no advantages with RTX on treatment safety. Conclusions: RTX has shown satisfactory characteristics in terms of efficacy and may be a promising treatment method for SDNS in children. However, the long-term effects have not been fully evaluated and should be further studied through randomized clinical trials.